Exploring the Structural Form and Interpretation in Writing Selected Tanaga - Rumusud, Michelle-Ann (International Journal of Arts, Sciences and Education, 2022)
Literature is an integral part of a race’s culture. An effective way to preserve literature is to analyze and interpret literary works. In this study, in-depth understanding will be examined in the selected tanaga’s according to the structural aspect and then made a thorough interpretation. It is important to study these forgotten tenets and make them the basis for future research and learning. It reflects the rich culture, experience, and beliefs that are considered as gems inherited from our ancestors. They should be kept alive in the heart and mind because they serve as a herald of true Filipino culture.